ANALISIS KELAYAKAN USAHATANI PADI VARIETAS INPARI 32 DI KELOMPOK TANI MARDI LESTARI DESA BUNGO KECAMATAN WEDUNG KABUPATEN DEMAK - Awami, Shofia Nur; Kafil, Ahmad; Widiyani, Aniya; Subantoro, Renan (Journal of Agribusiness, Social and Economic, 2024)
Bungo Village is one of the villages that produces the most rice in Wedung District. This research aims to determine total costs, revenues, income, BEP and the feasibility of farming based on the RC ratio value. In determining the sample of respondents using the probability random sampling method involving a sample of 30 respondents. Based on lan ownership status, namely own lan (proprietary rights), leased land and sharecropped land, so the research shows that the total costs incurred for rice farming per planting season per hectare consecutively are Rp 14,043,000,-, Rp. 22,793,000,- and Rp. 13,969,000,-. Revenue from rice farming is Rp. 37,092,600,-, Rp. 34,489,800,- and Rp. 16,402,300,-. Rice farming income is Rp. 23,703,600,-, Rp.13,783,800,- and Rp. 8,427,300,-. BEP units are 2,600.5 kg, 4,220.9 kg and 2,586.9 kg. BEP price Rp. 2,044.4, Rp. 3,568.7 and Rp. 2,104.1. The RC ratio values are 2.64, 1.51 and 1.5 respectively, which means that Inpari 32 variety rice farming is worth the effort.